BERPIKIR KRITIS-KREATIF SEBAGAI DIMENSI PROFIL PELAJAR PANCASILA PADA BUKU BAHASA INDONESIA KELAS VII KURIKULUM MERDEKA - Sofiyatunnisa, Junita; Susanto, Gatut (Hiski Malang, 2022)
Critical-creative thinking is a dimension of the Pancasila student profile that needs to be improved and applied to students so that they are able to face various problems that will be faced and are able to produce original and innovative ideas and works. This research aims to find out and describe the elements of critical-creative thinking contained in the Indonesian Language Book for Class VII Merdeka Curriculum and how these elements are presented therein. The type of this research is descriptive qualitative research. The data in this research are in the form of phrases and sentences that show the critical-creative thinking dimensions of the Pancasila student profile. The data source in this research is a class VII middle school Indonesian language book. The results of the research show that all the critical-creative thinking elements of the Pancasila student profile are contained in the Indonesian Middle School class VII book. The elements of critical-creative thinking are all presented verbally through stories/reading texts, learning materials, and questions/challenges.